2013
DOI: 10.1021/ie402039y
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Foaming of Poly(lactic acid) Blown with Compressed CO2: Influences of Long Chain Branching and Induced Crystallization on Foam Expansion and Cell Morphology

Abstract: In this study, poly(lactic acid) (PLA) resins with linear (L-PLA) and branched structure (B-PLA) were selected, and the solid state foaming technology was applied to prepare PLA foams. B-PLA foams exhibited a high expansion ratio of about 40 and cell density of 10 5−6 cells/cm 3 , whereas L-PLA foams only had the highest expansion ratio of 29.8 and cell density of 10 3−6 cells/cm 3 . When PLA resins were induced crystallization during CO 2 saturation, however, the prepared L-PLA foams presented the highest exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…Naja 39 et al prepared linear PLA foams, and it was observed that the collapse and coalescence of cells was serious at high temperature just as our results, and, Ren 16 et al found that even when chain extender was added, the PLA foams possessed a cell diameter more than 200 mm and cell density less than 2 Â 10 5 cell per cm 3 at 120 C. In our cases, the introduction of longchain branching structure could offset the plasticization of CO 2 to a certain extent, thus the cell diameter decreased (no more than 100 mm) and cell density increased (more than 2 Â 10 5 cell per cm 3 ) even at 150 C. However, the increasing viscosity caused by the TMPTA still couldn't prevent the coalescence at high temperature. The crystallization behavior of samples also affects the cell morphology.…”
Section: Effect Of Time On Foaming Behavior Of Lcb-plasupporting
confidence: 84%
See 1 more Smart Citation
“…Naja 39 et al prepared linear PLA foams, and it was observed that the collapse and coalescence of cells was serious at high temperature just as our results, and, Ren 16 et al found that even when chain extender was added, the PLA foams possessed a cell diameter more than 200 mm and cell density less than 2 Â 10 5 cell per cm 3 at 120 C. In our cases, the introduction of longchain branching structure could offset the plasticization of CO 2 to a certain extent, thus the cell diameter decreased (no more than 100 mm) and cell density increased (more than 2 Â 10 5 cell per cm 3 ) even at 150 C. However, the increasing viscosity caused by the TMPTA still couldn't prevent the coalescence at high temperature. The crystallization behavior of samples also affects the cell morphology.…”
Section: Effect Of Time On Foaming Behavior Of Lcb-plasupporting
confidence: 84%
“…1,[9][10][11] To reduce the cost and improve the mechanical properties of PLA, foaming technology is usually considered, 12 and the PLA foams are thought to be a promising material to replace polystyrene (PS) foams. 13 In recent years, many studies have focused on the low temperature foaming of PLA, [14][15][16] but the use of melt foaming processes, such as bead foaming and continuous extrusion foaming, is signicant especially in industry due to their high efficiency. However, the high temperature employed during melt foaming would be a big challenge for PLA due to its poor melt strength.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically homologous chains with linear and branched structures may reveal different properties. For PLA, branching is reported to influence rheological properties such as complex viscosity and elastic modulus and consequently its melt processing . Also different reports exist regarding the effect of branching on PLA chain dynamics or segmental mobility, glass transition and nucleation which may accelerate or delay the crystallization process as well as melting behavior and crystallization mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…But the cost of these nanoparticles are high, making it difficult to use them for the high-volume production of polymer foams [11]. Moreover, the foaming behavior of polymer was greatly influenced by the solubility of CO2 in melt polymer, which determines the cell morphology, expansion ratio, and crystallinity of the resultant foams [35][36][37]. Additionally, the use of supercritical fluid (SCF) can decrease the melt viscosity of the polymer during processing because of the plasticizing effect of the dissolved gas and thus can enhance the processability of polymers [11,22,35,36,38].…”
Section: Introductionmentioning
confidence: 99%